Evaluasi Pemborosan (7 Waste) dalam Proses Produksi PT XYZ dan Penerapan Lean Manufacturing 5S dan PDCA sebagai Solusi dalam Mengurangi Pemborosan - Try Rachmi Pemila Putri; Bambang Darmawan; Pebi Yuda Pratama (JURAL RISET RUMPUN ILMU TEKNIK, 2025)
This study aims to evaluate production waste at PT XYZ, a food manufacturing company in Bandung, Indonesia, which experiences inefficiencies caused by overproduction and product defects. A descriptive qualitative method with a case study approach was used, employing data from production reports, field observations, and interviews. The analysis was conducted using the 7 Waste framework, the 5S workplace organization method, and the PDCA (Plan-Do-Check-Act) cycle. The findings show that the main types of waste at PT XYZ are overproduction and defects, which are caused by inaccurate demand forecasting, ineffective layout, and inconsistent quality control. By implementing 5S and PDCA, the company successfully reduced waste, improved workspace organization, and increased process efficiency. This study provides practical insights for manufacturing companies seeking to implement lean strategies for continuous improvement.